2004
DOI: 10.2196/jmir.6.1.e7
|View full text |Cite
|
Sign up to set email alerts
|

Online Pediatric Information Seeking Among Mothers of Young Children: Results From a Qualitative Study Using Focus Groups

Abstract: BackgroundPre-natal and post-natal periods are times when many women actively seek health information from multiple sources, including the Internet. However, little is known about how pregnant women and mothers of young children seek and process online pediatric health information.ObjectiveTo explore why and where mothers of young children look for online health information and how they determine if the information they receive is trustworthy.MethodsFocus groups were conducted in a Southeastern US city to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
248
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(287 citation statements)
references
References 11 publications
18
248
0
8
Order By: Relevance
“…This is consistent with findings from our qualitative follow up interviews with parents where they reported engagement with the program was promoted by the credibility of the program source, the user friendly interface and tailoring of content and push notifications to baby's ages and key transition points. Our findings are congruent with existing research which suggests parents are increasingly relying on online source of information about infant feeding and care [23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with findings from our qualitative follow up interviews with parents where they reported engagement with the program was promoted by the credibility of the program source, the user friendly interface and tailoring of content and push notifications to baby's ages and key transition points. Our findings are congruent with existing research which suggests parents are increasingly relying on online source of information about infant feeding and care [23][24][25][26][27].…”
Section: Discussionsupporting
confidence: 90%
“…Evidence suggests that while parents increasingly rely on the internet for information on infant feeding and care [23][24][25][26][27] less research has been conducted on the use of smart phone apps in the post partum period. One study reported that low income women commonly use apps during pregnancy, but not in the post-partum period because of the limited availability of high quality apps, creating a 'post-partum app gap' [28].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of parents' health information sources reveal that parents use a large number and wide variety of sources such as newsletters, conferences, meetings, magazines and television [8,11]. Parents' information seeking patterns have been found to change over time and relate to their children's immediate needs and concerns [8,12,13] Lastly, parents gauge the quality of the information that is given to them and desire guidance when seeking health information independently [7,11,12,14]. These studies suggest that parents engage in many activities related to accessing information however how parents actually use health information in caring for their children or in working with health providers or teachers is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In plaats van het internet te diskwalificeren als informatiebron (zie Drayton et al, 2014) worden in studies over de kwaliteit van informatie op het internet vaak vier opties onderscheiden om de risico's van gebrekkige informatie tegen te gaan: het vergroten van de 'mediawijsheid' van de gebruiker (Bernhardt & Felter, 2004;Boston, Ruwe, Duggins, & Willging, 2005;Chen et al, 2000;Semere et al, 2003), het versterken van de verantwoordelijkheid van de beroepskrachten (D'Alessandro & Dosa, 2001;Nieuwboer, 2014;Sim et al, 2007), het hanteren van een 'gouden standaard ' (D'Alessandro & Kingsley, 2002;Hardwick & MacKenzie, 2003;Scullard, Peacock, & Davies, 2010) en het instellen van een keurmerk (Dornan & Oermann, 2006;HON).…”
Section: Discussieunclassified